Strategies to address conspiracy beliefs and misinformation on COVID-19 in South Africa: A narrative literature review - Nokwanda E. Bam (AOSIS, 2022)
Conspiracy theories and misinformation have been explored extensively however, strategies to minimise their impact in the context of coronavirus disease 2019 (COVID-19) vaccines are limited. This study aimed to explore strategies that can be used to reduce the negative effects of conspiracies and misinformation about SARS-CoV-2. This review was carried out based on accessed literature on beliefs in misinformation about the COVID-19 pandemic. A comprehensive search of databases, such as Google Scholar, EBSCOhost and African Journals between 2019 and 2022 yielded qualitative and quantitative studies. Two themes emerged, namely underlying motives for conspiracy theories and belief in misinformation about the pandemic and ways to overcome them. The latter included: (1) strengthening critical scanning of information, (2) critical review to address misinformation and (3) establishing approaches for managing conspiracy theories. A proposal is made to address conspiracy beliefs about COVID-19 infection. Contribution: This is believed to be the first review that describes strategies to mitigate belief in conspiracies and misinformation to promote vaccination.